Relevansi Good Corporate Governance, Struktur Kepemilikan, terhadap Kinerja Keuangan - Listya Sugiyarti; Sutandijo (Prisani Cendekia, 2022)
This study aims to determine the effect of good corporate governance and ownership structure on financial performance. The population in is study is the banking sector companies listed on the Indonesia Stock Exchange (BEI) from 2014 to 2018 as many as 46 companies. The sample of this study was determined by the purposive sampling method and obtained 11 banking companies listed on the Indonesia Stock Exchange from 2014 to 2018 so that the total sample amounted to 55 samples, but found as many as 16 sample data categorized as outlier data. So that from the 55 sample data there are only 39 samples left in this study. Testing the hypothesis in this study using multiple linear regression analysis. The results of this study indicate that good corporate governance which is proxied by the Asean Corporate Governance Scorecard has a significant effect on financial performance, while the ownership structure proxied by institutional share ownership has a significant effect on financial performance. This results can give important information to investors and also management that the market values more to corporates with good corporate governance practices. Meanwhile the market does not give emphasize to the institutional ownership factor